Creating a critical culture to cultivate students' critical thinking: a case study of a media literacy course in Japan. (15th March 2022) - Zhang, Xiaohong; Kubota, Kenichi; Kubota, Mayumi
The purpose of this study was to examine whether students critically thought about media and how a critical culture influences students' critical thinking in a media literacy course. This research used a media literacy course at a Japanese university as a case study. The authors collected data by participant observation. As a result, the authors found that: 1) the cycle, of thinking activities in the classroom, discussion on LMS and reflection activities, created a critical culture in a blended learning environment during one semester; 2) students improved their critical thinking through extensive experiences of media analysis and production; 3) five factors were important to cultivate students' critical thinking in the critical culture.